A Maize ZmAT6 Gene Confers Aluminum Tolerance via Reactive Oxygen Species Scavenging - Du, Hanmei; Huang, Ying; Qu, Min; Li, Yihong; Hu, Xiaoqi; Yang, Wei; Li, Hongjie; He, Wenzhu; Ding, Jianzhou; Liu, Chan; Gao, Shibin; Cao, Moju; et al. (Frontiers in Plant Science, 2020)
Aluminum (Al) toxicity is the primary limiting factor that affects crop yields in acid soil. However, the genes that contribute to the Al tolerance process in maize are still poorly understood. Previous studies have predicted that ZmAT6 is a novel protein which could be upregulated under Al stress condition. Here, we found that ZmAT6 is expressed in many tissues and organs and can be dramatically induced by Al in both the roots and shoots but particularly in the shoots. The overexpression of ZmAT6 in maize and Arabidopsis plants increased their root growth and reduced the accumulation of Al, suggesting the contribution of ZmAT6 to Al tolerance. Moreover, the ZmAT6 transgenic maize plants had lower contents of malondialdehyde and reactive oxygen species (ROS), but much higher proline content and even lower Evans blue absorption in the roots compared with the wild type. Furthermore, the activity of several enzymes of the antioxidant system, such as peroxidase (POD), superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX), increased in ZmAT6 transgenic maize plants, particularly SOD. Consistently, the expression of ZmSOD in transgenic maize was predominant upregulated by Al stress. Taken together, these findings revealed that ZmAT6 could at least partially confer enhanced tolerance to Al toxicity by scavenging ROS in maize.